2017
DOI: 10.1136/archdischild-2017-313414
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive trajectories from infancy to early adulthood following birth before 26 weeks of gestation: a prospective, population-based cohort study

Abstract: ObjectiveTo determine the trajectory of cognitive test scores from infancy to adulthood in individuals born extremely preterm compared with term-born individuals.DesignA prospective, population-based cohort study.Setting276 maternity units in the UK and Ireland.Patients315 surviving infants born less than 26 completed weeks of gestation recruited at birth in 1995 and 160 term-born classroom controls recruited at age 6.Main outcome measuresBayley Scales of Infant Development-Second Edition (age 2.5); Kaufman As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
155
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(177 citation statements)
references
References 36 publications
(20 reference statements)
15
155
2
2
Order By: Relevance
“…That is, the perinatal development of the brain is not complete before preterm birth, resulting in widespread disruptions in the frontoparietal network, 8 the integrity of which is associated with optimal executive function, processing speed, and intelligence. The lack of association between cognitive impairment and age at assessment implies that children born very prematurely do not 'catch up' with their termborn peers through childhood and adolescence; that is, children born preterm suffer from a deficit in cognition, not a delay, supporting the findings of Linsell et al, 90 who found no evidence of recovery or deterioration of cognitive function in extremely preterm individuals from infancy to young adulthood (also see Doyle and Anderson 91 for a review of adult outcomes of extremely premature birth). Furthermore, when the studies were split into subgroups of younger (4-10y) and older children (11-17y) effect sizes were very similar between groups, although moderating effects were found to be associated with study effect size in the younger children (birthweight was associated with intelligence study effect size, and continuous gestational age was associated with executive function study effect size).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…That is, the perinatal development of the brain is not complete before preterm birth, resulting in widespread disruptions in the frontoparietal network, 8 the integrity of which is associated with optimal executive function, processing speed, and intelligence. The lack of association between cognitive impairment and age at assessment implies that children born very prematurely do not 'catch up' with their termborn peers through childhood and adolescence; that is, children born preterm suffer from a deficit in cognition, not a delay, supporting the findings of Linsell et al, 90 who found no evidence of recovery or deterioration of cognitive function in extremely preterm individuals from infancy to young adulthood (also see Doyle and Anderson 91 for a review of adult outcomes of extremely premature birth). Furthermore, when the studies were split into subgroups of younger (4-10y) and older children (11-17y) effect sizes were very similar between groups, although moderating effects were found to be associated with study effect size in the younger children (birthweight was associated with intelligence study effect size, and continuous gestational age was associated with executive function study effect size).…”
Section: Discussionsupporting
confidence: 54%
“…The second implication of these findings is related to the non-significant correlations between age at assessment and the effect sizes of each study, and the consistent effect sizes between the younger and older subgroups. The lack of association between cognitive impairment and age at assessment implies that children born very prematurely do not 'catch up' with their termborn peers through childhood and adolescence; that is, children born preterm suffer from a deficit in cognition, not a delay, supporting the findings of Linsell et al, 90 who found no evidence of recovery or deterioration of cognitive function in extremely preterm individuals from infancy to young adulthood (also see Doyle and Anderson 91 for a review of adult outcomes of extremely premature birth).…”
Section: Discussionsupporting
confidence: 54%
“…Because few quality long-term longitudinal studies exist, the answer is unclear. In Archives of Disease in Childhood , Linsell and colleagues addressed this important question using data from the EPICure study,1 which assessed cognitive functioning at 2.5, 6, 11 and 19 years of age in survivors born <26 weeks’ gestational age in the UK and the Ireland over 10 months in 1995. Their major finding was that poor cognitive function in EP survivors persists throughout childhood into late adolescence/early adulthood.…”
mentioning
confidence: 99%
“…The third Editorial in this issues relates to the article on the cognitive trajectories of extremely preterm infants by Louise Linsell and colleagues that was published in the April issue of the main edition of the journal 1. The article described cognitive assessments of preterm infants who were born before 26 weeks of gestation and then assessed using age standardised intruments at 2 to 3 years (Bayley), 6 to 9 years (Kauffman) and 19 years (Wechsler).…”
Section: Cognitive Trajectories From Infancy To Early Adulthood Follomentioning
confidence: 99%